Research Progress in Computational Methods for System-Level Coupling of Electromagnetic Pulse - Haiyan Xie; Jianguo Wang (IEEE Access)
This paper reviews recent system-level analysis methods for electromagnetic pulse coupling with local and network systems. For local systems, starting from the electromagnetic topology (EMT) method which utilizes the Baum-Liu-Tesche (BLT) equation, the time-domain BLT equation and the transient EMT method are reviewed. Their abilities to analyze nonlinear systems are examined. The transient EMT method is not only applicable to nonlinear cases but can also be easily integrated with circuit or device analysis. For large network systems, direct analysis presents significant challenges. A simplified method based on the effective coupling length approach and its application in high-altitude electromagnetic pulse coupling with power grids are discussed. This simplified method reduces the complexity of analysis from $N^{2}$ to N, where N represents the number of lines in the network. Additionally, a prediction model that utilizes artificial neural networks (ANN) for HEMP coupling with overhead lines is presented. Finally, the challenges faced in system-level coupling analysis are outlined and suggestions for future research are offered.